Anti-Viral Potential and Modulation of Nrf2 by Curcumin: Pharmacological Implications - Mahdie Rahban; Mehran Habibi-Rezaei; Mansoureh Mazaheri; Luciano Saso; Ali A. Moosavi-Movahedi (MDPI AG, 2020)
Nuclear factor erythroid 2-related factor 2 (Nrf2) is an essential transcription factor that maintains the cell's redox balance state and reduces inflammation in different adverse stresses. Under the oxidative stress, Nrf2 is separated from Kelch-like ECH-associated protein 1 (Keap1), which is a key sensor of oxidative stress, translocated to the nucleus, interacts with the antioxidant response element (ARE) in the target gene, and then activates the transcriptional pathway to ameliorate the cellular redox condition. Curcumin is a yellow polyphenolic curcuminoid from Curcuma longa (turmeric) that has revealed a broad spectrum of bioactivities, including antioxidant, anti-inflammatory, anti-tumor, and anti-viral activities. Curcumin significantly increases the nuclear expression levels and promotes the biological effects of Nrf2 via the interaction with Cys151 in Keap1, which makes it a marvelous therapeutic candidate against a broad range of oxidative stress-related diseases, including type 2 diabetes (T2D), neurodegenerative diseases (NDs), cardiovascular diseases (CVDs), cancers, viral infections, and more recently SARS-CoV-2. Currently, the multifactorial property of the diseases and lack of adequate medical treatment, especially in viral diseases, result in developing new strategies to finding potential drugs. Curcumin potentially opens up new views as possible Nrf2 activator. However, its low bioavailability that is due to low solubility and low stability in the physiological conditions is a significant challenge in the field of its efficient and effective utilization in medicinal purposes. In this review, we summarized recent studies on the potential effect of curcumin to activate Nrf2 as the design of potential drugs for a viral infection like SARS-Cov2 and acute and chronic inflammation diseases in order to improve the cells' protection.